Study on smoke spreading behavior under multi-point centralized smoke extraction in tunnel fires - Houlin Ying; Weibing Jiao; Zhisheng Xu; Jiaming Zhao; Zihan Yu (Case Studies in Thermal Engineering)
In this work, the effect of various exhaust parameters on the smoke propagation laws under the multi-point centralized exhaust mode are investigated through numerical simulations. The research variables include heat release rate (HRR), exhaust volume, vent spacing, and total area of open vents. Results show that increasing the exhaust volume decreases the maximum temperature rise (ΔTmax), while increasing the other three factors increases the maximum temperature rise. The longitudinal temperature of the smoke below the tunnel ceiling shows an exponential decay. The exhaust vent velocity is influenced by the exhaust fan, exhibiting an W-shaped distribution. Moreover, the exhaust efficiency of the system improves with increasing extracted volume, but decreases as HRR, vent spacing, and total area of open vents increase. Eventually, the predictive model for the dimensionless back-layering length under multi-point centralized smoke extraction was developed through theoretical analysis. The results indicate that the backflow length becomes larger with increasing HRR, while it decreases with the increase in the other three variables. The results can provide a reference for understanding the smoke behavior under multi-point centralized smoke exhaust, and offer guidance for smoke control, determination of safe evacuation zones, and firefighting rescue.